Implementing shared decision making in the NHS: lessons from the MAGIC programme. (18th April 2017) - Joseph-Williams, Natalie; Lloyd, Amy; Edwards, Adrian; Stobbart, Lynne; Tomson, David; Macphail, Sheila; Dodd, Carole; Brain, Kate; Elwyn, Glyn; Thomson, Richard
Abstract : Shared decision making requires a shift in attitudes at all levels but can become part of routine practice with the right support, say Natalie Joseph-Williams and colleagues